Indonesian Interference in Javanese and Conversely to the Dialogue of the Main Character in the Film Yowis Ben 1 - Astantiya Sabarani; Farida Nugrahani; Dewi Kusumaningsih (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Interferensi merupakan salah satu fenomena kontak bahasa. Interferensi dapat terjadi dalam segala tataran kehidupan, termasuk di dalam dialog oleh tokoh utama dalam sebuah film. Penelitian ini bertujuan untuk mendeskripsikan interferensi bahasa Indonesia ke dalam bahasa Jawa dan sebaliknya pada dialog tokoh utama dalam film “Yowis Ben 1” dan implementasinya sebagai alternatif materi ajar bahasa Indonesia di SMA. Metode yang digunakan adalah deskriptif kualitatif. Interference is one of the phenomena of language contact. Interference can occur at all levels of life, including in dialogue by the main character in a film. The aims of this research are to describe the interference of Bahasa into Javanese and vice versa, based on the dialogue of the main character in "Yowis Ben 1" film and its implementation to become the teaching material alternative in SMA (Senior High School).This research belongs to qualitative. The technique of collection data is documentation. Test the data validity is using triangulation sources. Data analysis is selecting the data which have been gathered through the records, notes and transcription then describing the results of the research on language interference in “Yowis Ben 1” movie. The analysis result shows the use of Indonesian language in a movie called “Yowis Ben 1” interference on the phonology, morphology, syntax, and semantics level.The factors causing the interference in the use of Indonesian by the main character in the film "Yowis Ben 1" are bilingualism, low loyalty in the recipient's language user, and the habit of using the mother tongue.